2000
DOI: 10.1093/bja/85.5.696
|View full text |Cite
|
Sign up to set email alerts
|

Giving long-persistent starch as volume replacement can cause pruritus after cardiac surgery

Abstract: We reviewed the prevalence and severity of pruritus in 85 patients after cardiac surgery. EloHAES, a long-lasting hydroxyethylated starch, was given to 59 of these patients. None of the patients who did not receive EloHAES developed pruritus, compared with 22% of those who did (P = 0.007). The timing of onset, duration and severity of the pruritus are similar to those found previously for other hydroxyethylated starches, and the cause of this pruritus is likely to be similar. Hydroxyethyl starch can cause long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 18 publications
1
38
0
2
Order By: Relevance
“…Kimme et al 12 have demonstrated in a retrospective study involving 37 patients operated for cerebral aneurysm and treated with 10% HES 200/0.5 (i.e., an average molecular weight of 200 kDa and a molar substitution of 0.5) that incidence and severity of pruritus were significantly higher for a total infused HES volume larger than 500 g. Total infused volume varied between 50 and 1,950 g and the global incidence of pruritus was 54%. Morgan et al 11 have also underlined this relationship. Eighty-five patients were reviewed retrospectively after cardiac surgery.…”
Section: Hes and Pruritusmentioning
confidence: 93%
See 2 more Smart Citations
“…Kimme et al 12 have demonstrated in a retrospective study involving 37 patients operated for cerebral aneurysm and treated with 10% HES 200/0.5 (i.e., an average molecular weight of 200 kDa and a molar substitution of 0.5) that incidence and severity of pruritus were significantly higher for a total infused HES volume larger than 500 g. Total infused volume varied between 50 and 1,950 g and the global incidence of pruritus was 54%. Morgan et al 11 have also underlined this relationship. Eighty-five patients were reviewed retrospectively after cardiac surgery.…”
Section: Hes and Pruritusmentioning
confidence: 93%
“…This is not a surprise since pruritus following HES administration frequently develops tardily and is generally observed only with higher cumulative doses exceeding 200 g. 10,12,13,[16][17][18][19] However, other studies, which were not prospective and randomized, have assessed a possible link between the administration of HES and the development of pruritus. These studies show a very variable incidence of pruritus, varying between 0-54 %, [8][9][10][11][12][13][16][17][18][19][20] and a link between the total amount of HES infused and the incidence and severity of pruritus. 10,12,13,[16][17][18][19] In patients who are developing pruritus after HES administration, itching usually starts with a delay of 3 days to 15 weeks.…”
Section: Hes and Pruritusmentioning
confidence: 99%
See 1 more Smart Citation
“…Pruritus associated with HES was reported in 14 studies involving a total of 2598 patients, of whom 2173 (83.6%) received HES and 425 (16.4%) did not. * The odds of pru-*References 45,52,53,55,58,59,76,84,86,95,96,99,105,106. ritus were significantly increased by HES exposure ( Table 5).…”
Section: Pruritusmentioning
confidence: 99%
“…Itching after using HES remains a debatable topic [18][19][20] . Special features of HES-induced pruritus include long latency of onset and persistence.…”
Section: Pruritusmentioning
confidence: 99%